U-Pb zircon geochronology of the Galway Granite, Connemara, Ireland:: implications for the timing of late Caledonian tectonic and magmatic events and for correlations with Acadian plutonism in New England - Feely, Martin; Coleman, Drew; Baxter, Sadhbh; Miller, Brent (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT The Galway Granite occupies a key location in the Caledonides of western Ireland. The 80 km long, WNW-trending axis of the batholith lies astride and stitches the EW-trending Skerd Rocks Fault, a splay of the orogen-parallel Southern Uplands Fault. The Skerd Rocks Fault separates high-grade metamorphic rocks of the Connemara Massif from Lower Ordovician greenschist-facies metavolcanic and metasedimentary rocks. We present new isotopic U-Pb zircon age determinations, using thermal ionisation mass spectrometry (TIMS), for ﬁve granite samples from the central block of the Galway Granite. Early coeval diorite and granite magmas are concomitant with the development of pure ﬂattening fabrics and are succeeded by emplacement of a suite of generally unfoliated granites intruded in a brittle fracture regime. The results of the U-Pb zircon geochronology (G1 = 394.4 ± 2.2 Ma; G2~402 Ma; G3 = 397.7 ± 1.1 Ma; G4 = 399.5 ± 0.8 Ma) indicate that the emplacement of the early suite occurred over at least 8 Ma and belongs to the Late Emsian stage. Samples of commingled diorite (G3) and granite (G4) yield ages that are indistinguishable within error. Sample G5 is from an alkali feldspar leucogranite that cuts the early suite. Zircon from this granite yielded a U-Pb age of 380 ± 6 Ma and a single concordant monazite yielded 383.6 Ma, indicating emplacement at the Givetian-Frasnian boundary and a gap of ~20 Ma between intrusion of the two granite suites. These data provide constraints on the timing of ﬁnal movement on the orogen-parallel strike-slip Southern Uplands-Skerd Rocks Fault System, and have implications for correlations between Acadian plutonism in New England and in western Ireland.